2012
DOI: 10.1210/jc.2011-3056
|View full text |Cite
|
Sign up to set email alerts
|

PROKR2 Variants in Multiple Hypopituitarism with Pituitary Stalk Interruption

Abstract: We report PROKR2 variants in congenital hypopituitarism with pituitary stalk interruption, suggesting a potential role of the prokineticin pathway in pituitary development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 22 publications
2
56
0
1
Order By: Relevance
“…Interestingly, renal agenesis has not been reported in patients with PROKR2 mutations (30). This study confirms the high phenotypic heterogeneity of disorders associated with PROKR2 and PROK2 loss of function mutations (31,32).…”
Section: Discussionsupporting
confidence: 79%
“…Interestingly, renal agenesis has not been reported in patients with PROKR2 mutations (30). This study confirms the high phenotypic heterogeneity of disorders associated with PROKR2 and PROK2 loss of function mutations (31,32).…”
Section: Discussionsupporting
confidence: 79%
“…Given the roles of PROK2 and PROKR2 in angiogenesis, it was plausible to consider that mutations of such genes could be observed in patients with PSIS. Our group reported for the first time three heterozygous PROKR2 variants (L173R, R85H, A51T) in patients with GH, TSH and ACTH deficiencies (in some of them); MRI showed PSIS in all patients (20). Later on, McCabe et al reported five other PROKR2 variants (p.A51T, p.R85L, p.L173R, and p.R268C, p.G371R) in 11 patients with SOD and congenital hypopituitarism (from isolated GH deficiency to panhypopituitarism).…”
Section: Novel Aetiologies Involving Actors Known To Be Associated Wimentioning
confidence: 88%
“…Pathogenic germline PROKR2 mutations associated with central hypogonadism have been identified to cause modulation of distinct intracellular pathways (biased signaling modulation) (Libri et al 2014, Sbai et al 2014, whereby the PROKR2 wild type activates different G-protein subtypes (Chen et al 2005). PROKR2 variants have been further described in patients with idiopathic combined pituitary hormone deficits (CPHD) including gonadotropin deficiency (Raivio et al 2012, Reynaud et al 2012. The PROKR2 also forms constitutive homomers in vivo ( Marsango et al 2011), and specific protomer-protomer interfaces for the oligomer have been suggested ( Sposini et al 2015).…”
Section: R68 Reviewmentioning
confidence: 99%